2007
DOI: 10.2174/138161207780487566
|View full text |Cite
|
Sign up to set email alerts
|

Restoring the Dysfunctional Endothelium

Abstract: Nowadays the endothelium is considered a key determinant of vascular health. NO is the principal mediator of all endothelial protective effects, due to its antiinflammatory, antiproliferative, immunomodulatory and vasorelaxant properties. On the contrary, a growing body of evidence suggests that endothelial dysfunction is associated with cardiovascular events. Emerging data suggest that acute coronary syndromes (ACS) may involve a complex interplay between endothelial dysfunction, inflammation and thrombosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 218 publications
2
24
0
Order By: Relevance
“…This balance is impaired in hypercholesterolemia and atherosclerosis. 20,21 Endothelial dysfunction, reflected by impaired endothelium-dependent relaxation, occurs in experimental models of hypercholesterolemia, as was confirmed in WT mice of this study. 22,23 Similarly, many clinical studies reported abnormal endothelium-dependent vasodilation in hypercholesterolemic patients.…”
Section: Discussionsupporting
confidence: 80%
“…This balance is impaired in hypercholesterolemia and atherosclerosis. 20,21 Endothelial dysfunction, reflected by impaired endothelium-dependent relaxation, occurs in experimental models of hypercholesterolemia, as was confirmed in WT mice of this study. 22,23 Similarly, many clinical studies reported abnormal endothelium-dependent vasodilation in hypercholesterolemic patients.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, if future studies confirm that Endo_PAT RHI measurements are associated with patients' acute cognitive outcomes, endothelial function monitoring may serve as a prognostic tool in the ICU as well as a means to study the impact of therapies aimed at reducing brain dysfunction through interventions that enhance endothelial function (e.g., statin pharmacotherapy, early physical rehabilitation). 45 Our results are also in agreement with the growing body of literature examining tissue perfusion abnormalities as measured by near-infrared spectroscopy. Consistently low tissue oxygenation was associated with worse organ failure in small cohorts of critically ill patients, 46 and lower tissue oxygen saturation and slower recovery rate after an ischemic period has been correlated to perfusion abnormaities.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies have revealed a protective effect of statins against vascular disease risk, including a reduction of systemic inflammation and improvement in endothelial dysfunction. [16][17][18] Furthermore, statins have been shown to exert many pleiotropic effects, [19][20][21] which could explain, at least in part, the greater reduction in cardiovascular risk with statin use than other LDL-lowering modalities. 22,23 The ability of statins to stabilize the culprit lesions of atherosclerotic plaque and prevent them from rupturing has also been demonstrated in symptomatic coronary arteries [24][25][26] and extracranial carotid arteries.…”
Section: Discussionmentioning
confidence: 99%